IMPROVEMENT IN PRODUCTION AND QUALITY OF WHEAT UNDER ORGANIC NUTRIENT MANAGEMENT - R. D. SHINDE,; V.P. PARMAR,; D.G. JONDHALE,; B.N. KOLAMBE,; K.G. PATEL, (The Bioscan, 2014)
An experiment was conducted with twelve treatment combinations of organic N levels and organic liquid formulations along with one outside chemical control to find the effect of organics on yield and quality of wheat at Certified Organic Farm, ACHF, Navsari Agricultural University, Navsari during 2011-12 and 2012-13. These treatments were replicated thrice in factorial randomized block design. It was found that all the yield and quality parameters were increase with increase in recommended dose of N through BC:VC:CC. The treatments receiving application of 100% BC:VC:CC (O3) and spraying of 1% enriched banana pseudostem sap (S1) significantly increased the grain and straw yield of wheat as well as protein and dry gluten content as compared to rest of the treatments containing organics N levels and different organic liquid formulations, respectively. While, organics treatment found beneficial in producing higher yield and better quality of wheat.